2020
DOI: 10.1038/s41419-020-02819-w
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor antagonizes Wnt/β-catenin signaling in colorectal tumorigenesis

Abstract: Farnesoid X receptor (FXR, encoded by NR1H4), a critical regulator of bile acid homeostasis, is widely implicated in human tumorigenesis. However, the functional role of FXR in colorectal cancer (CRC) and the precise molecular mechanism remain unclear. In this study, we demonstrated that FXR expression was downregulated in colon cancer tissues and decreased expression of FXR predicted a poor prognosis. Knockdown of FXR promoted colon cancer cell growth and invasion in vitro, and facilitated xenograft tumor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…The would-healing assays were carried out as described previously. 33 Cells were cultured in six-well plates until 90% confluence. Pipette tips (10 µL) were then utilised to scratch artificial vertical lines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The would-healing assays were carried out as described previously. 33 Cells were cultured in six-well plates until 90% confluence. Pipette tips (10 µL) were then utilised to scratch artificial vertical lines.…”
Section: Methodsmentioning
confidence: 99%
“…The transwell assays were carried out as described previously. 33 Briefly, cells, suspended in FBS-free medium, were seeded into Transwell (Corning, New York, NY, USA) inserts coated with Matrigel (BD Biosciences, Franklin Lakes, NJ, USA) or not. The lower chamber contained 600 μl of RPMI-1640 medium with 20% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data revealed that abnormal bile acid metabolism was involved in CAC development. Several studies have found that the FXR mRNA expression is inversely correlated with CRC progression, and FXR deficiency increased the tumor load in Apc min/+ mice and xenograft tumor model [47][48][49]. Moreover, mice lacking FXR showed disrupted intestinal epithelium integrity and an overgrowth of intestinal bacteria [50].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the activation of FXR by GW4064 decreased the expression of HER2, the upstream of JAK/STAT3 pathway 47 . Besides JAK/STAT signalling, OCA might exert tumour suppressor role by directly regulating FXR target genes SHP 31 and MMP7 48 or suppressing Wnt/β‐catenin 49 and EGFR/ERK signalling 50 . Hence, OCA exerts its tumour suppressor functions via multiple molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%